2019
DOI: 10.3389/fpsyg.2019.01852
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mindset Can Reduce the Adverse Effect of Substance Use on Adolescent Reasoning

Abstract: The present study examined the relationship between substance use and reasoning in adolescents, and further investigated the modulation role of growth mindset on this relationship. A total of 1759 adolescents in China with substance use experience were investigated. The results showed that substance use (smoking, drinking, and illicit drug use) was negatively correlated with reasoning ( r = −0.24 ∼−0.39, p < 0.01) and growth mindset ( r = −0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It was found that all values ranged from 1.68 to 2.01, and there was no problem as none exceeded 10. The results demonstrated that the CMV was not a serious threat, so the data are suitable for other analyzes (Harris and Mossholder, 1996; Wang et al. , 2019).…”
Section: Methodsmentioning
confidence: 86%
“…It was found that all values ranged from 1.68 to 2.01, and there was no problem as none exceeded 10. The results demonstrated that the CMV was not a serious threat, so the data are suitable for other analyzes (Harris and Mossholder, 1996; Wang et al. , 2019).…”
Section: Methodsmentioning
confidence: 86%
“…Few studies linked growth mindset to alcohol outcomes (for a review see [22]). Most studies were correlational and showed that the growth mindset generally appeared to be negatively linked to alcohol use [23][24][25][26][27]. Studies which linked mindset and addiction outcomes (including alcohol abuse) focused on a wide range of mindsets (e.g., addiction mindset, intelligence mindset, morality mindset, substance abuse mindset, drinking tendencies mindset, alcoholism mindset, etc.).…”
Section: Growth Mindset and Alcohol Outcomesmentioning
confidence: 99%
“…Growth mindsets proactively defend against the negative effects that are associated with substance abusers (Wang et al, 2019). Additionally, having a growth mindset substantially increases an individual's reasoning ability which, in turn, decreases their likelihood of drug abuse (Wang et al, 2019).…”
Section: Benefits Of Growth Mindsetmentioning
confidence: 99%
“…Growth mindsets proactively defend against the negative effects that are associated with substance abusers (Wang et al, 2019). Additionally, having a growth mindset substantially increases an individual's reasoning ability which, in turn, decreases their likelihood of drug abuse (Wang et al, 2019). Within places of employment, positive expectations are found within individuals with growth mindsets which results in a sense of belonging in their workplace, greater satisfaction with their workplace, and better relationships with coworkers and bosses (Rattan & Dweck, 2018).…”
Section: Benefits Of Growth Mindsetmentioning
confidence: 99%